Utility of the Cobas® Taqman® Ct Test, v2.0 for the detection of circulating strains of Chlamydia Trachomatis in Mexico - López-Hurtado, Marcela (2022)
Objective: This study aimed to evaluate the usefulness of the qPCR de COBAS® TaqMan® CT test to detect circulating strains in Mexico. Materials and Methods: Descriptive and transversal study. We analyzed 413 endocervical cases for the COBAS® system of patients with infertility, with the diagnosis of C. trachomatis. that acudieron has the Clínica ETS del Instituto Nacional de Perinatología (INPer) in the Ciudad de México. Las muestras positivas también analizaron por el sistema Abbot Real-time CT / NG, y por PCR de punto final para la detección de plásmido. Las variables de estudio fueron: Infertilidad, diagnóstico de Chlamydia trachomatis, infección por Chlamydia y otras variables. To determine the association between CT infection and clinical data, Fisher's no parametric exact test was used. A value p<0.05 was considered significant. Results: Of the 413 deaths, 276 female patients with primary infertility and 137 with secondary infertility, they ranged from 20 to 42 years. The main cause of primary infertility is endocrine-ovarian factor and secondary infertility is tuboperitoneal factor. Of 22 positive cases, a significant association between infertility by tubárico factor and infection by C. trachomatis (RR = 2.47 95% CI 1.1-5.5, p <0.05) was demonstrated by COBAS prueba ® TaqMan® CT. De éstas solo 5 fueron identificadas por el sistema Abbott (p <0.011). Conclusion. El sistema de COBAS® TaqMan® CT de Roche Molecular Diagnostic mostró mayor utilidad para identificar las cepas de CT que están circulando en México. Conclusion: The COBAS® TaqMan® CT test from Roche Molecular Diagnostic showed more utility in identifying the CT strains that circulate in Mexico.